OXYTOCIN DOSE ANALYSIS OF BREASTMILK PRODUCTION THROUGH INDUCTION LABOR - Sara Nurmala; Cantika Zaddana (Journal of Science Innovare, 2019)
Breast milk is the only first food that can be consumed by newborns until the age reaches six months. therefore it is very important to know by the mother who is pregnant and will give birth about the importance of breast milk. Oxytocin drugs have similar functions to the natural hormone oxytocin produced by the body. This drug serves to trigger or strengthen the contraction of the uterine muscle. Therefore, oxytocin can be used to stimulate (induce) labor and stop bleeding after childbirth. In addition, this drug can also help stimulate the release of breast milk in breastfeeding mothers. Oxytocin should be avoided by pregnant women who can not give birth normally, for example because it has a narrow pelvis, suffering from placenta previa, or having a too strong uterine contractions. Oxytocin is also prohibited for pregnant women with cephalopelvic disproportion, impaired fetal conditions, uterine damage, or a history of caesarean section. In this study we see whether there is effect of different doses of oxytocin on the quantity of breastmilk produced. oxytocin doses were administered with 3 doses of 5 UI, 10 UI and 15 UI. the dose of oxytocin is administered once per incidence of labor. maternal results obtained by oxytocin induction of 5 UI and 10 UI obtained breastmilk averaging 10 ml in the first 24 hours after delivery. and a mother with oxytocin induction 15 UI received an average breastmilk of 10 ml at 24 hours after delivery.